A maneuverable underwater vehicle for near-seabed observation - Kaixin Liu; Mingxuan Ding; Biye Pan; Peiye Yu; Dake Lu; Siwen Chen; Shuo Zhang; Gang Wang (Nature Communications)
Abstract Underwater robots can collect comprehensive information on species and habitats when conducting seabed operations, enhancing localized insights and expanding underwater ecological understanding. One approach uses autonomous underwater vehicles, but proximity operations may disturb sediments and compromise observation quality. Another approach uses wheeled or legged benthic robots, but unavoidable contact limits their application in delicate ecosystems like coral reefs. To address these challenges, we propose a maneuverable underwater vehicle for near-seabed observations. This vehicle moves with minimal turbulence and shows strong resistance to external disturbances, enabling high-quality seabed observation as close as 20 cm. It rapidly detects intense disturbances like turbulence and wall effects, allowing real-time path planning to prevent bottoming. Multiple tests in various marine environments, including sandy areas, coral reefs, and sheer rock, show low sediment disturbance and improved adaptability to rugged underwater terrain.